The behaviour of reinforced concrete squat wall - Deng, Jianzhong (2016)
The objective of this study is to investigate the behaviour of non-rectangular RC squat walls, which are commonly used in low-rise buildings. It is important to access the performance of these walls when subjected to seismic waves because they served a crucial role in providing the lateral stiffness and strength of a building or structure. In direction of the objective, an experimental program was conducted using four L-shaped squat walls. The walls were subjected to different loading directions and different axial load ratio. Their performance for each case was also accessed in terms of secant stiffness, strength capacity, displacement components, curvature, crack patterns and failure mode. To validate the observations from the experimental results and further explore the behaviour of, a parametric study containing 72 cases were done using a proved-reliable non-linear finite element analysis tool (Diana). The parameters are axial load ratio, lateral loading directions, shear span ratio and longitudinal reinforcement ratio were also included as. Lastly, the effects of all parameters on the behaviour of walls are studied and concluded.